Research landscape of exosomes in platelets from 2000 to 2022: A bibliometric analysis - Zhan, Min; Shi, Shengnan; Zheng, Xiaoyu; Chen, Wenjie; Sun, Linjuan; Zhang, Yehao; Liu, Jianxun (Frontiers in Cardiovascular Medicine, 2022)
Background Blood-derived exosomes are involved in developing multiple pathological processes, with platelets being the most well-known source. Related studies have become an area of research with significant value and potential. However, no bibliometric studies in this field have yet been identified. We aimed to analyze the hotspots and academic trends of platelet exosome research through bibliometric visualization to actively grasp the research base in this field and track its developmental orientation. Methods From 2000 to 2022, we screened all relevant publications on platelet exosome-related research from the Web of Science database, generated knowledge maps using VOSviewer and CiteSpace software, and analyzed research trends in the field. Results A total of 722 articles were screened for inclusion based on the search strategy. The number of articles on exosome studies in platelets has expanded vastly. The USA and the People’s Republic of China contributed substantially among 69 countries or regions. Amsterdam University and Semmelweis University are the research institutions with the most publications. The most studied and co-cited journals were the International Journal of Molecular Sciences and the Journal of Extracellular Vesicles. We identified 4,598 authors, with Nieuwland Rienk having the highest number of articles and Bruno Stefania having the most cited publications. Keywords of great interest include “thrombosis,” “anti-inflammatory,” “anti-apoptosis,” “angiogenesis,” “microparticles,” “miRNAs,” “stem cells,” and “biomarkers,” which are key research areas for future development. Conclusion We used bibliometric and visualization methods to identify hotspots and trends in platelet exosome research. Platelet exosome research is widely expanding. Future research will most likely focus on “thrombosis,” “anti-inflammatory,” “anti-apoptosis,” “angiogenesis,” “microparticles,” “miRNAs,” “stem cells,” and “biomarkers.”